THE ROLE OF INFORMATION AND COMMUNICATION TECHNOLOGY (ICT) IN THE EDUCATION OF HISTORY TO DEVELOP NATIONALISM - Munir, - (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2009)
In the globalization era today and by having pluralistic conditions of Indonesia—by having many ethnic diversity, languages, culture, custom, religion and different ways of life based on social economics; each region requires the education of history be able to collect, manage, store, analyze, verify and disseminate important information effectively and efficiently in order to develop nationalism. The presence of Information and Communication Technology (ICT) is hoped to facilitate the education of history so that history can be complete, accurate, fast and modish. This article will explain how the role of ICT can facilitate the education of history in developing nationalism supported by information literacy.